Implementation of Quality Management towards the Internal Service Quality and Trust in Management and its Impact on Job Satisfaction: The Role of Moderation of the National Health Insurance System - Pane, Ridwan Tonny Hasiholan; Setyadi, Djoko; Rosnani, Titik (International Review of Management and Marketing, 2022)
This research aims to explain the effects of the Implementation of Quality Management towards the Internal Services quality and Trust in Management and its Impact on Health Workers’ Job Satisfaction and to examine the role of moderation variable of the national health insurance system. The method used in this study was quantitative and research participants were health workers who work in 20 health centers with 365 health workers. The data were analyzed using the statistical method of Structural Equation Modeling with the WarpPLS approach. The results of the study found that the implementation of quality management had a significant effect on (1) internal service quality, (2) trust in management, (3) health workers’ job satisfaction, (4) internal service quality had a significant effect on trust in management, (5) internal service quality had a significant effect on the mediation of the implementation of quality management towards health workers’ job satisfaction (6) trust in management had a significant effect on the mediation of the implementation of quality management towards health workers’ job satisfaction (7) the national health insurance system had a significant effect on the moderation of the quality of internal service towards health workers’ job satisfaction (8) the national health insurance system had a significant effect on the moderation of trust in management towards health workers’ job satisfaction.